Cervical length screening among low-risk women; relationship of body mass index on cervical length and risk of preterm birth - Basri, Nurul Iftida; Dasrilsyah, Rima Anggrena; Mohd Jamil, Amilia Afzan; Leong, Charmaine Sook Yee (BioMed Central, 2024)
Background: Preterm birth (PTB) contributes to nearly 11% of all deliveries in the world. The majority of spontaneous preterm birth (sPTB) remains unexplained. Risk factors include abnormal body mass index (BMI), short cervical length, comorbidities and many more. However, there is limited study on the association between body mass index, cervical length and preterm birth in Malaysia among low-risk women. Hence, we aim to examine the relationship between body mass index, cervical length and the risk of spontaneous preterm birth. Method: In this prospective cohort study, pregnant women between 16 and 24 weeks who fulfilled the criteria were recruited. Women with history of preterm birth were excluded. Demographic and clinical data (age, BMI, ethnicity, education level and parity) were obtained. Cervical length was measured using transvaginal scan. Patients were then followed up till delivery to determine their delivery gestation and outcome of delivery. Results: Out of 153 women who participated in this study, 146 women had cervical length of more than 30 mm, six had cervical length between 25 mm and 30 mm and one had cervical length of 24 mm. There were nine (9) cases of sPTB, with all of them being late preterm with normal midtrimester cervical length. Almost half of them (44%) were overweight/obese. A significant association was found between age, cervical length, and parity compared to BMI. Nevertheless, no significant association was seen between the BMI and risk of sPTB. Conclusion: This study demonstrates a higher BMI is associated with longer cervical length, but it is not necessarily protective against sPTB. Hence, we concluded there is a limited role in cervical length screening among low-risk women regardless of their BMI in predicting sPTB.